CORRECTION OF TRANSVERTEBRAL MICROPOLARIZATION OF PAIN SYNDROME AND FUNCTIONAL CHANGES IN THE NERVOUS SYSTEM IN PATIENTS WITH AXIAL SPINE DEFORMATIONS - Tadjiev, M.M. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Objective: Examination and conservative therapy were performed in 181 patients with axial spinal deformities and the effectiveness of transvertebral micropolarization of pain syndrome and functional changes in the nervous system in this category of patients was revealed. Material and methods: When studying the functional state of peripheral nerves performed by the stimulation method ENMG. Electrical stimulation of the tibial nerve was performed in the popliteal fossa, the M response and the H response were recorded. Results: Thus, as a result of our studies, it was found that in patients with ADP it is possible to identify moderate pain syndrome according to the YOUR scale, moderate changes in the nervous system of the scoring according to the SCHBVNS, an imbalance of the autonomic nervous system with a predominance of sympathicotonia, and a decrease in impulses for motor and sensory ways. Conclusion: a mild pain syndrome with detectable motor, sensory disturbances and changes in the autonomic nervous system in the form of a predominance of sympathicotonia.